DEVELOPING ENGLISH SURVIVORS: A VOCABULARY LEARNING GAME FOR EFL LEARNERS - Taofix Rahman; Mutiarani Mutiarani (LPPM Universitas Islam Darul `Ulum Lamongan, 2025)
This study outlines the design, implementation, and evaluation of English Survivors, an instructional media developed to support EFL learners in intentional vocabulary acquisition using digital gaming principles. The implementation, following the ADDIE model, incorporates quizzes and immediate feedback to enhance vocabulary retention and support learner motivation. An iterative refinement cycle included a pilot study with five learners, succeeded by a controlled classroom implementation involving fifteen participants, and concluded with external validation by experts in educational media and linguistics. Quantitative analysis indicates that 88% of participants considered the vocabulary tasks relevant, 86.67% valued immediate feedback, and 85.34% responded positively to the quiz-based format. A media expert assigned a functionality score of 39 out of a possible 40, with the content expert awarded 40 out of 40. The evidence collectively supports the platform's operational viability and motivational capacity. Statistically significant vocabulary gains, along with trials in authentic instructional settings, support the theory that pedagogical games designed through systematic methods and refined through iterative user and expert evaluation is possible, when integrated into controlled instructional frameworks, significantly improve vocabulary mastery.